Tradition Beyond Formal Fiqh: Ethnic Perspectives on Negotiating Kafāʾah in Marriage within the Aceh Singkil Community - Zuhrah, Fatimah; Sugiyarto, Wakhid; Marpuah, Marpuah; Khalikin, Ahsanul; Fauzah, Titi Isnaini (Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
The emphasis on customary law within the Aceh Singkil community, alongside the application of fiqh (Islamic jurisprudence) in religious practices, raises important questions regarding the formation of legal realities in practice. This article explores the social considerations underlying legal practices, focusing on the role of ethnic identity within the Aceh Singkil community. The study employs a qualitative methodology to achieve this objective, utilizing in-depth interviews and document analysis as data collection techniques. The data are analyzed through a structural-functional sociological approach, conceptualizing legal practice as a social phenomenon. The findings reveal that ethnic-based collective consciousness significantly influences the community’s tendency to prioritize customary law over formal fiqh rulings when determining kafāʾah (equality) criteria in marriage. This emphasis is evident in applying economic and occupational standards, the prohibition of intra-clan marriage, and the disregard for the religious status of a partner’s parents. These standards are shaped by concerns for individual rights, the preservation of ancestral heritage, and the promotion of social harmony as part of a broader nation-building initiative. Nevertheless, the Aceh Singkil community continues to uphold fiqh norms, particularly the requirement that both spouses share the same religion, demonstrating that Islamic law remains an integral part of the collective consciousness, operating alongside customary norms. These findings affirm that the implementation of law within ethnic communities is grounded in a collective consciousness—shaped by both religious and customary elements—which serves as a foundation for constructing and sustaining social solidarity. [Penekanan terhadap hukum adat dalam komunitas Aceh Singkil, yang juga menerapkan norma fikih dalam praktik keagamaannya, menimbulkan persoalan terkait pembentukan realitas hukum yang berlaku. Artikel ini bertujuan untuk mengungkap berbagai pertimbangan sosial dalam praktik hukum, dengan menitikberatkan pada peran identitas etnis dalam komunitas Aceh Singkil. Untuk mencapai tujuan tersebut, artikel ini menggunakan metode kualitatif dengan teknik pengumpulan data melalui wawancara mendalam dan dokumentasi. Data dianalisis menggunakan pendekatan sosiologi struktural-fungsional yang memandang penerapan hukum sebagai suatu fenomena sosial. Hasil temuan menunjukkan bahwa kesadaran kolektif berbasis etnis memengaruhi kecenderungan untuk lebih mengutamakan hukum adat dibandingkan dengan ketentuan fikih dalam menetapkan kriteria kesetaraan (kafāʾah) dalam pernikahan. Penekanan ini tercermin dalam penetapan standar kesetaraan berbasis ekonomi dan pekerjaan, larangan pernikahan dalam satu marga, serta pengabaian status agama orang tua pasangan. Penentuan standar tersebut mempertimbangkan perlindungan hak individu, pelestarian warisan leluhur, dan pembentukan harmoni sebagai bagian dari proyek kebangsaan. Meskipun demikian, komunitas Aceh Singkil tetap mempertahankan norma fikih, khususnya persyaratan seagama bagi pasangan, yang menunjukkan bahwa hukum Islam merupakan bagian integral dari kesadaran kolektif yang berjalan sejajar dengan hukum adat. Temuan ini menegaskan bahwa penerapan hukum dalam masyarakat etnis bertumpu pada kesadaran kolektif, baik yang dibentuk oleh agama maupun adat, sebagai fondasi dalam membangun dan mempertahankan solidaritas sosial.]